2016
DOI: 10.1161/strokeaha.115.011401
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Length Estimation on Delayed Gadolinium–Enhanced T1

Abstract: Background and Purpose Previous studies revealed a close relationship between thrombus length and recanalization rate after intravenous thrombolysis (IVT). As a novel approach, we prospectively adjusted the order of sequence acquisition to obtain delayed gadolinium-enhanced T1 (dGE-T1) and thereby assess thrombus length on dGE-T1 to evaluate its predictive value for recanalization after IVT. Methods We reviewed prospectively collected clinical and imaging data from acute ischemic stroke patients with middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Recently Yan et al presented evidence that thrombus lengths can be assessed on delayed gadolinium-enhanced T1 images in patients with MCA occlusion 23. This supports our assumption that depicting the distal terminus of the thrombus by means of contrast agent is beneficial in thrombus length assessment.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Recently Yan et al presented evidence that thrombus lengths can be assessed on delayed gadolinium-enhanced T1 images in patients with MCA occlusion 23. This supports our assumption that depicting the distal terminus of the thrombus by means of contrast agent is beneficial in thrombus length assessment.…”
Section: Discussionsupporting
confidence: 83%
“…However, the method of thrombus length assessment differed remarkably in both studies (native thin slice CT versus contrast-enhanced MRA). Methodological differences may also explain substantial differences to results from Yan et al , using a slice thickness of 5 mm in delayed gadolinium-enhanced 2D T1-sequence to estimate thrombus lengths 23. Patients with poor outcome had thrombi with an optimal cut-off value of 7.7 mm.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple studies have shown that a longer thrombus length, greater thrombus volume, and higher clot burden are predictive of IV t-PA failure in achieving successful recanalization, as well as of poor neurological outcome 1 2 4 8. The prognostic value of such clot characteristics on recanalization achieved with mechanical thrombectomy approaches has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…P revious studies have demonstrated that characteristics of thrombus, especially thrombus length, were closely related to the rate of recanalization, clinical outcome after intravenous thrombolysis (IVT), 1 and even stroke etiology in patients with acute ischemic stroke with large-artery occlusion (LAO). 2,3 However, the dynamic changes of the thrombus after IVT and how the remaining thrombus affects clinical outcome in human stroke are still poorly understood.…”
mentioning
confidence: 99%
“…Delayed gadolinium-enhanced T1 (dGE-T1), which can delineate the distal end of the thrombus and avoid blooming artifacts of the susceptibility vessel sign, was proved a useful tool for accurate measurement of thrombus length when combined with time-of-flight MR angiography. 1 Similarly, 4D CT angiography, derived from CT perfusion, can not only outline intracranial thrombi better than conventional single-phase CTA 6 but also evaluate collateral flow with increased sensitivity. 7 Therefore, we designed this study with the following objec-tives: 1) to assess the change of thrombus length in patients with LAO without recanalization at 24 hours after IVT detected on dGE-T1 and 4D-CTA derived from CTP, 2) to evaluate the relationship between the changing of thrombus length and collaterals, and 3) to find the influencing factors of different changing patterns of thrombus length.…”
mentioning
confidence: 99%